Who Will Fight for Us? Union Designated Women´s Advocates in Auto Manufacturing Workplaces - Woodhall, Julia R.; Leach, Belinda (Just Labour: A Canadian Journal of Work and Society, 2010)
Women´s employment in traditionally male manufacturing jobs is hindered by both formal and informal structures (Levine 2009). In light of recent recession-based changes in the Ontario economy, it is becoming more important for women to maintain well-paying manufacturing employment. Women face different challenges in the home and workplace than men. This paper investigates the Canadian Auto Workers´ (CAW) Union´s unique women´s advocacy program, as a promising mechanism to secure women´s safety at home and at work, while protecting their employment status. Drawing on ethnographic research with women auto workers and union women, our findings suggest that the CAW´s women´s advocacy program is innovative and beneficial in maintaining women´s employment as they attend to personal problems. This program can be extended throughout other locals and unions to assist women dealing with violence and other issues related to work-life experience.